Planetary Protection for Mars: Time for Reconsideration - Alexandrov, Svetoslav (Bangladesh Journal of Bioethics, 2016)
In this manuscript I discuss the ethics of the protection of hypothetical organisms on Mars in terms of upcoming manned space missions and subsequent colonization.